Social Entrepreneurship in Islamic Perspective Role of Islamic Values, Environmental Values and Social Enterprise Attitudes - Kurjono, Kurjono; Juliana, Juliana; Kamil, Anton Abdulbasah; Mardiani, Rika; Setiawan, Yana; Samlawi, Faqih (Islamic Research, 2025)
The purpose of this research is to analyze the influence of Islamic values, environmental values, and social entrepreneurial attitudes on the social entrepreneurial intentions of Indonesian students. The research population consists of all UPI students from various faculties. Meanwhile, for the sample size of the research, 160 UPI students who have taken entrepreneurship courses were selected. Data collection was conducted using a questionnaire distributed via a Google Form link. The research results show that Islamic values and environmental values have a positive and significant impact on social entrepreneurship intentions. Islamic values have a positive and significant impact on social entrepreneurship, and environmental values also have a positive and significant impact. Similarly, social entrepreneurship attitudes have a positive and significant impact on social entrepreneurship intentions. Social entrepreneurship attitudes mediate the influence of Islamic values on social entrepreneurship intentions and mediate the influence of environmental values on social entrepreneurship intentions. Thus, social entrepreneurship attitudes partially mediate both variables, namely Islamic values and environmental values. Based on these findings, it is necessary to revitalize the entrepreneurship education curriculum by incorporating aspects of social entrepreneurial attitudes into entrepreneurship courses at universities. Maintaining guidance for students on environmental values and enhancing social entrepreneurship attitudes through socially-based business activities.